LAG-3 Contribution to T Cell Downmodulation during Acute Respiratory Viral Infections - Linmar Rodríguez-Guilarte; Mario A. Ramírez; Catalina A. Andrade; Alexis M. Kalergis (Viruses, 2023)
LAG-3 is a type I transmembrane protein expressed on immune cells, such as activated T cells, and binds to MHC class II with high affinity. LAG-3 is an inhibitory receptor, and its multiple biological activities on T cell activation and effector functions play a regulatory role in the immune response. Immunotherapies directed at immune checkpoints, including LAG-3, have become a promising strategy for controlling malignant tumors and chronic viral diseases. Several studies have suggested an association between the expression of LAG-3 with an inadequate immune response during respiratory viral infections and the susceptibility to reinfections, which might be a consequence of the inhibition of T cell effector functions. However, important information relative to therapeutic potential during acute viral lower respiratory tract infections and the mechanism of action of the LAG-3 checkpoint remains to be characterized. In this article, we discuss the contribution of LAG-3 to the impairment of T cells during viral respiratory infections. Understanding the host immune response to respiratory infections is crucial for developing effective vaccines and therapies.